Синдром Рубінштейна-Тейбі у поєднанні з хворобою мойамойа - Зелінська, Н. Б.; Хорошая, О. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article describes a clinical case of the girl with dwarfism as a result of the Rubinstein-Teybi syndrome in combination with growth hormone deficiency. The patient was treated with growth hormone therapy during four years, which led to normalization of her growth. After 4 years was diagnosed the Moyamoya disease.